DIMENSI JENDER DALAM HUKUM KEWARISAN ISLAM - Fathuddin Aziz (Yurisprudentia: Jurnal Hukum Ekonomi, 2015)
Islamic law is often perceived not gender sensitive and put women in a position of subordination of men. There are a number of rules that position women are not equal to men. Rules of inheritance for example, which gives the portion of the female part is only half of the portion of the male part is a form of gender bias . Yet this is precisely the aspect of women's inheritance elevated by one rank from its original position that did not get a part , even a part of the estate itself , be equal to men , both became heir . Besides, there are many verses of the Quran that tells us about the subject of equality of men with women in the provisions of Islamic law